Flexible pressure sensors: modeling and experimental characterization - Sepúlveda, A. T. (2012)
Flexible capacitive pressure sensors fabricated with nanocomposites were experimentally characterized and results compared with simulations from analytical modeling. Unlike traditional diaphragm silicon pressure sensors, the flexible nanocomposite sensors present a linear response over a large pressure range due to the changes in the volume of the dielectric that cause the pressure inside the dielectric cavity to change. Several devices with different geometries were used and the model results compare well with the experimental data. Sensitivities ranging from 2.5- 20 fF/kPa were obtained and the devices dynamic response show a dual behavior, i.e., response time of the sensor during a pressure decreasing step is lower than for a pressure increasing step. This comportment is explained by the viscoelastic behavior of the PDMS-based nanocomposites used for fabrication of the capacitive sensor electrodes.